Comprehensive evaluation of sensory taste acceptance, consumer preference and palatability factors in vitamin B (B1, B6 and B12): insights from a sensory analysis study - Akhter, Fouzia; Shormi, Farzana Rabin; Alam, A. S. M. Monirul (International Journal of Research in Medical Sciences, 2026)
Background: Vitamins B1, B6 and B12 are essential for neurological and metabolic health, but their sensory properties may affect compliance. This study evaluated the sensory palatability and consumer response to a Vitamin-B supplement. Methods: A cross-sectional sensory analysis was carried out over six months among 400 participants selected using standardized inclusion criteria at Central Hospital Limited, Dhaka, Bangladesh. Sensory attributes were evaluated using the Modified Mason and Nottingham 9-point scale. Consumer behavior outcomes and statistical analyses, including correlations and internal consistency, were conducted. Ethical approval and informed consent were strictly maintained according to the study protocol. Results: The sample consisted mostly of females (70%) and participants aged 26–35 years. Prior vitamin-B use was reported by 64%. Sensory evaluation showed high acceptability, with odor (mean 7.23), appearance (6.87), aftertaste (7.41) and general approval (7.10) scoring positively. Overall palatability averaged 7.0±0.5, with 94–95% of responses falling within the “like” category, except for aftertaste, which showed more neutral ratings (29%). Consumer responses were highly favourable: 87.5% rated overall liking ≥7, 85.5% expressed definite purchase intent and 87% were willing to recommend the product. Strong correlations were observed between aftertaste and general approval (r=0.82) and palatability significantly predicted purchase intent (r=0.65, p<0.001). Sensory scale reliability was excellent (Cronbach’s α=0.89). Conclusions: The Vitamin-B (B1, B6 & B12) showed high sensory acceptability, strong consumer satisfaction and solid purchase and recommendation intent. Aftertaste and odour strongly influenced overall approval. About 95% of participants genuinely liked the product, reflecting excellent sensory acceptance and consumer appeal.